Fourier-transform near-infrared spectroscopy first application to age determination in European fish species: the case of the Atlantic horse mackerel from the central Mediterranean Sea - Basilone, Gualtiero; Lo Cicero, Gabriella; Fortuna, Miryam; Luviner, Anita; Ferreri, Rosalia; Aronica, Salvatore; Genovese, Simona; Giacalone, Giovanni; Fontana, Ignazio; Bonanno, Angelo (Frontiers in Marine Science, 2024)
Fourier-Transform Near Infrared Spectroscopy (FT-NIRS) has recently been used to reduce the processing time for estimates of annual age in several fish species. The present study represents the first application of this technique to marine organisms from the European waters. Atlantic horse mackerel (Trachurus trachurus) from the central Mediterranean Sea was selected for its ecological role, its socioeconomic value and because its age is regularly estimated by otolith reading under stereomicroscope for stock assessment purposes. Absorption spectra of the whole otoliths were acquired by FT-NIRS across a multiyear dataset, obtained during acoustic surveys carried out in different regions of the central Mediterranean Sea. The acquired spectra were processed to optimize calibration models to predict age. The best linear models obtained by the optimizing procedure, predicted age successfully with a coefficient of determination of 0.95-0.96, mean squared error 0.5 years, and bias <0.03 years. Although, regional calibration models were also obtained separately, the models with all regions combined appeared much more robust and encompassing the whole age range, suggesting its usefulness for the entire spatial distribution range considered in the preset study. The use of FT-NIRS allowed to successfully predict age for horse mackerel between the ages 1 and 14, with similar or better precision (and bias) of the traditional methods, also increasing the standardization by repeatability of age assignments. The preliminary results obtained by this study encourage further effort to fine-tune the calibration model for new species, in order to apply a precise, rapid, cost-effective method for stock assessment purposes of Mediterranean fish resources.